The potential of Barringtonia asiatica Biopesticide from Papua to Eradicate Pests in Aquaculture - Achmad Suhermanto; Fabian Ardianta; Murtihapsari Murtihapsari; Achmad Sofian (Jurnal Airaha, 2022)
Saponins are compounds derived from plants that are currently widely used in aquaculture for aquatic pest control. In this study, potential saponin components extracted from fish poison tree (Barringtonia asiatica), which is widely dispersed in tropical areas worldwide, were characterized. Saponin properties were obtained from seeds and leaves by extraction and spectrophotometric methods. To test its properties, four different concentrations of saponin extracts, namely 10 ppm, 20 ppm, 30 ppm, and 40 ppm, were applied in four trials containing 20 tilapias each. An unexpected result was obtained and proved that the saponins extracted from the seeds of the fish poison tree proved to be significantly more effective than the saponins extracted from the peel of its fruit to eradicate pest in pond. The results also revealed that the lethal dose of saponins reached higher level at a concentration of 40 ppm. It can be concluded that fish poison tree as a poisonous tree plays an important role in ensuring the sustainability of saponin stocks. The use of natural materials such as fish poison tree as a biopesticide has the potential to minimize environmental damage and reduce costs for aquaculture.